L’Épigraphie ibérique du pays valencien et sa comparaison avec la Catalogne (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article is set up out of a DEA presented in Toulouse (France) in 2003. We intend to study of the iberic epigraphy of País Valenciano,  between the Vth and the Ist century b. C. and to compare it with Mª I. Panosa’s results for Catalonia. We have collected all the inscriptions published in the MLH III (regions F and G) in order to link archeological contexts and emergence of writing. Concerning the supports, we can conclude that there’s no continuity of use throughout  the  mediterranean coast and that in the Levante, writing wasn’t as used for trade as in the Northeastern part of the peninsula.